The Cuba-US bilateral relationship : new pathways and policy choices - Kelly, Michael J., 1968-; Moreno, Erika; Witmer, Richard C., 1966- (New York, NY : Oxford University Press, 2019)
This work brings together experts from across three disciplines - politics, economics, and law - to address the key issues that affect Cuba-U.S. bilateral relations today. The chapters identify the opportunities and challenges presented to both nations in each of their respective disciplines while staking out what the future may hold.
Also issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on September 12, 2019).
Keywords: United States -- Foreign relations -- Cuba; Cuba -- Foreign relations -- United States; Politics and Government; Politics & government